2000
DOI: 10.1093/pcp/41.4.391
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Jasmonate- and Salicylate-Related Signaling Pathways for the Production of Specific Herbivore-Induced Volatiles in Plants

Abstract: We compared volatiles from lima bean leaves (Phaseolus lunatus) infested by either beet armyworm (Spodoptera exigua), common armyworm [Mythimna (Pseudaletia) separata], or two-spotted spider mite (Tetranychus urticae). We also analyzed volatiles from the leaves treated with jasmonic acid (JA) and/or methyl salicylate (MeSA). The volatiles induced by aqueous JA treatment were qualitatively and quantitatively similar to those induced by S. exigua or M. separata damage. Furthermore, both S. exigua and aqueous JA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
179
0
8

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(191 citation statements)
references
References 31 publications
4
179
0
8
Order By: Relevance
“…We previously reported that both JA and SA signaling pathways were activated in lima bean plants in response to TSSM damage (Ozawa et al 2000). Choh et al (2004) showed that not only JA but also benzo-(1,2,3)-thiadiazole-7-carbothioic acid S-methyl ester (BTH), a functional analog of SA, applied to the soil of potted lima bean plants reduced the numbers of eggs laid on those plants.…”
Section: Nsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that both JA and SA signaling pathways were activated in lima bean plants in response to TSSM damage (Ozawa et al 2000). Choh et al (2004) showed that not only JA but also benzo-(1,2,3)-thiadiazole-7-carbothioic acid S-methyl ester (BTH), a functional analog of SA, applied to the soil of potted lima bean plants reduced the numbers of eggs laid on those plants.…”
Section: Nsmentioning
confidence: 99%
“…Hopke et al 1994;Ozawa et al 2000;Arimura et al 2009). For example, Hopke et al (1994) found that treating lima bean (Phaseolus lunatus L.; Fabaceae) with JA increased the emission of volatiles similar to the HIPVs released by leaves infested with either two-spotted spider mites (TSSMs), Tetranychus urticae C.L.…”
Section: Introductionmentioning
confidence: 99%
“…Dicke et al 1990a;Turlings et al 1990;Scutareanu et al 1997;Du et al 1998); (3) pathways for biosynthesis of compounds in blends of HIPV exist in the plants and are shown to be inducible by herbivory (e.g. Paré et al 1999;Bouwmeester et al 1999); (4) blends of HIPV not only emanate from the leaf under attack by the herbivore, but are also systemically induced in the plant (Turlings and Tumlinson 1992;Dicke 1994;Guerrieri et al 1999); (5) application of jasmonic acid (JA), a phytohormone, to wild-type plants or defence-signalling mutants leads to production of volatiles similar to HIPV (Hopke et al 1994;Ozawa et al 2000;Gols et al 2003;Thaler et al 2002;Van Poecke and Dicke 2003;Ament et al 2004); (6) herbivore-induced gene expression patterns in plants are similar to those mediated by jasmonates (e.g. Kant et al 2004;Ament et al 2004;Mercke et al 2004;Reymond et al 2004); (7) elicitors of HIPV synthesis in the plant have been found in the regurgitate/saliva of herbivores [N-(17-hydroxylinolenoyl)-L-glutamine or volicitin: Alborn et al 1997Alborn et al , 2000β-glucosidase: Hopke et al 1994;Mattiacci et al 1995]s.…”
Section: Introductionmentioning
confidence: 99%
“…A significant number of these studies have, however, been dedicated to metabolic profiling specifically of the nonvolatile compounds involved in primary plant metabolism using gas chromatography (GC) coupled to mass spectrometry (MS). Another significant part of the plant metabolome, comprising the volatile metabolites, is of a particular interest, since they play an important role in fundamental processes such as signaling mechanisms and interorganism interactions (Shulaev et al, 1997;Seskar et al, 1998;Ozawa et al, 2000;Arimura et al, 2002;Liechti and Farmer, 2002;Dicke et al, 2003;Dudareva et al, 2004;Engelberth et al, 2004;Ryu et al, 2004). In addition, these components are also of great agronomic importance as volatile metabolites are major determinants of food and flower quality in terms of flavor and fragrance (Buttery and Ling, 1993;Baldwin et al, 2000Baldwin et al, , 2004Yilmaz et al, 2001;Tandon et al, 2003;Krumbein et al, 2004;Simkin et al, 2004;Ruiz et al, 2005).…”
mentioning
confidence: 99%